ANALISIS PENENTUAN PRIORITAS PENANGANAN JALAN DI KOTA DENPASAR BERDASARKAN METODE ANALYTIC HIERARCHY PROCESS (AHP) DENGAN KOMBINASI METODE FUZZY ANALYTIC HIERARCHY PROCESS (FAHP) DAN TOPSIS - Wira Savitri, Dwi Ayu; Wedagama, D. M. Priyantha; Suparsa, I G. Putu (JURNAL SPEKTRAN; Vol. 3, No. 1, Januari 2015DO - 10.24843/SPEKTRAN.2015.v03.i01.p06)
Abstrac :Road handling priority determination is an important tasks faced by decision makers and is regarded as a complex multi-criteria problem. It requires a system to categorise and ranks the project order using several criteria. Officially, SK. No. 77 of the Directorate General of Highway issued in 1990 is a method used in the local government. This method however, has been considered to have limitations to determine road handling priority. Using previous studies, the Analytic Hierarchy Process (AHP) and the combination of FAHP and TOPSIS methods are considered relevant to determine road handling priority. These methods incorporates a variety of criteria which can also be considered by the decision makers. Using the AHP, the criteria of road conditions, traffic volume, economic and policy factors are 41.8%, 25.4%,  21.6 and 11.2% respectively. Meanwhile, a combination methods of FAHP and TOPSIS give the criteria of road conditions, traffic volume, economic and policy factors of 33.8%, 26.6%, 24.7% and 14.9% respectively. Both AHP and FAHP produce the same result in terms of criteria rank. This is not the case however, in the sub criteria rank. This study found that AHP gives road handling priority differently to the SK. No 77 of Directorate General of Highway (1990). In contrast, a combination methods of FAHP and TOPSIS produces road handling priority in the same way to the SK. No 77 of Directorate General of Highway (1990). Denpasar city government is suggested to consider the use of FAHP and TOPSIS method in determining its road handling priority. This method is considered to have a capability to combine many criteria using a priority weighted score. The road handling priority results therefore, are more realistic.
Keywords: The priority of road handling, AHP, Fuzzy AHP, TOPSIS